Implementasi Sanksi Pidana Terhadap Pelaku Tindak Pidana Penghinaan Terhadap Jokowi Presiden Republik Indonesia Melalui Media Sosial - adika, adika karim (Diktum: Jurnal Ilmu Hukum, 2021)
The research problem is why the perpetrator committed the criminal act of insulting Jokowi, the President of the Republic of Indonesia through social media. How to implement criminal sanctions against perpetrators of criminal acts of insulting Jokowi, the President of the Republic of Indonesia through social media. According to the results of the research on the factors causing the perpetrator to commit hate speech crimes on social media, among others, the psychological factors of the individual itself can cause crimes such as emotional power, low mental health, hurt with the victim, revenge, the public's ignorance factor is also the cause of hate speech crimes. especially the insults committed on social media. The implementation of criminal sanctions for cases in this study is that after paying attention to the criminal elements the defendant has been convicted of a criminal act of insulting the President according to the prosecutor's demands. The defendant was proven to have fulfilled the elements of Article 207 of the Criminal Code. The research method uses a normative and empirical juridical approach, the normative juridical approach is carried out by studying norms or rules, while the empirical approach is carried out by interviewing the sources. Efforts to further examine the Crime of Insulting the President, for example the Articles of President Defamation which can be aggravated. The quality of the crimes of humiliation of the President continues to increase. Therefore, it is necessary to improve facilities and infrastructure in law enforcement. This includes improving the capacity of law enforcement officers, namely: Police, prosecutors, judges and advocates, for example in mastery of information technology. To be able to anticipate or at least minimize criminal acts of insulting the President, the government, especially Judges, must firmly impose sanctions in the form of heavier penalties for each perpetrator of the president's insult so that the sanctions given can actually have a clear effect on those who have done them and can make fear for a person who has not committed a criminal act of insulting the President. The research problem is why the perpetrator committed the criminal act of insulting Jokowi, the President of the Republic of Indonesia through social media. How to implement criminal sanctions against perpetrators of criminal acts of insulting Jokowi, the President of the Republic of Indonesia through social media. According to the results of the research on the factors causing the perpetrator to commit hate speech crimes on social media, among others, the psychological factors of the individual itself can cause crimes such as emotional power, low mental health, hurt with the victim, revenge, the public's ignorance factor is also the cause of hate speech crimes. especially the insults committed on social media. The implementation of criminal sanctions for cases in this study is that after paying attention to the criminal elements the defendant has been convicted of a criminal act of insulting the President according to the prosecutor's demands. The defendant was proven to have fulfilled the elements of Article 207 of the Criminal Code. The research method uses a normative and empirical juridical approach, the normative juridical approach is carried out by studying norms or rules, while the empirical approach is carried out by interviewing the sources. Efforts to further examine the Crime of Insulting the President, for example the Articles of President Defamation which can be aggravated. The quality of the crimes of humiliation of the President continues to increase. Therefore, it is necessary to improve facilities and infrastructure in law enforcement. This includes improving the capacity of law enforcement officers, namely: Police, prosecutors, judges and advocates, for example in mastery of information technology. To be able to anticipate or at least minimize criminal acts of insulting the President, the government, especially Judges, must firmly impose sanctions in the form of heavier penalties for each perpetrator of the president's insult so that the sanctions given can actually have a clear effect on those who have done them and can make fear for a person who has not committed a criminal act of insulting the President.